Nursing Student Perceptions About The Role Of The Tutor And Implementation Of The Tutorial Process Using The Seven Jumps Technique - Syafrizal Syafrizal (Jurnal Ilmiah Keperawatan Indonesia (JIKI), 2021)
Seven jumps is an approach used in the problem solving learning method or Problem Based Learning (PBL). The seven jumps technique implemented using the tutorial method directed by a tutor. The tutor's role is one of the critical factors for the success of the tutorial process. Students' perceptions of the tutor's role will affect the pros and cons of implementing tutorials. Therefore, it is necessary to test the role of the tutor and implementation of the tutorial process. The purpose of this study was to find the perceptions of nursing students about the role of the tutor and implementation of the tutorial process using the seven jumps technique. This study used a descriptive design. The population in this study was students of the regular program of the Faculty of Nursing, University of Riau. The sample in this study amounted to 222 people who recruited using simple random sampling technique. The measuring instrument used is a questionnaire made by researchers using google from which has been test for validity and reliability. This study shows that for the tutor role there are 114 respondents (51.4%) who have positive perceptions and 108 respondents (48.6%) have negative perceptions. As for implementation of the tutorial process, there were 117 respondents (52.7%) who had positive perceptions and 105 respondents (47.3%) had negative perceptions. This research expected to test the learning process and optimize the tutor's role in implementing tutorials using the seven jumps technique. Keywords: Student Perceptions; Tutor; Seven Jump Technique